WEB-BASED LEARNING MODEL USING HOT POTATOES APPLICATIONS TO INCREASE LANGUAGE STUDENT ACHIEVEMENT - Fansury, Andi Hamzah; Agreani, A Vivit; Lutfin, Nursamsilis (PEOPLE: International Journal of Social Sciences, 2018)
The aim of this research was generally (1) to know the implementation of web-based learning model using hot potatoes application to increase language student achievement (2) to know student interest in web-based learning model by using hot potatoes application to increase language student achievement. This research used quasi experimental method. This research was conducted at second grade students of Junior High School 8 Makassar with 850 students’ population. The writer used a random sampling technique. The total sample used was 60 students. The researcher divides the sample into two classes: the experimental class and the control class. Instruments research used is test, questionnaire and interview. Web-based learning model using hot potatoes application can help students develop their language ability. Web-based learning model using hot potatoes application is very effective to be applied to avoid boredom and boredom of students in following the learning process